O patrimônio museológico universitário: a formação das coleções da Universidade Federal de Lavras - UFLA - Mendes, Patricia Muniz (2020)
This research aims to present a study about collections formation, arrangement, and exhibition to the public in universities spaces. The chosen theme came from the desire to understand university collections structure, encompassing both collection and the collector, such as their motivations and their conditions on selecting and receiving, as well vicissitudes that it went through until being placed in the university museum. Inserted in the university space, of the aforementioned typology and in this time frame, as an option was decided to investigate the museological heritage of the Federal University of Lavras (UFLA), through the case studies: Museu Bi Moreira (MBMUFLA) and the Museu de História Natural (MHN -UFLA). These case studies selection sought to enhance the research of different typology collections on university and how have been displayed to society. Regarding the theme delimitation, the preference for university museum heritage was also motivated by the following reasons: first by their nature - they are university collections, of local and regional scope; and, second, its exhibition in the public sphere and university museum space. This last factor, at MBMUFLA, determined a transference of collection usufruct of the private to the public, and implementation of a new management model for university tutelage. The Case study elected allows realizing that stands a panoramic scenario, in which two variables distinguished in the collections formation and musealization in this University. While at the MHN-UFLA the collection was built over time and the vicissitudes of the University itself, on the other hand, the MBM-UFLA collections were formed from a particular disposition but have taken on a public dimension through musealization.